IMPLEMENTASI PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN DITINJAU DARI NILAI DASAR EKONOMI ISLAM (STUDI PADA PKH DI DESA KAMBUNO KECAMATAN BULUKUMPA KABUPATEN BULUKUMBA) - hamdi, Hasniar; Fathurrahman, Fathurrahman; Sirajuddin, Sirajuddin (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Bulukumba Regency is one of the districts that has welfare problems (poverty), one of which is in the village of Kambuno. this village is one of the villages that received social assistance in the form of the Family Hope Program (PKH). The purpose of this study is to find out, understand and explain how the implementation of the Family Hope Program (PKH) improves people's welfare when viewed from the basic values of Islamic economics in Kambuno Village. The type of research used is